Underwater early strength filler
By using specific formulas of underwater early strength fillers in underwater construction, the problem of insufficient strength of concrete when pouring underwater is solved, high early strength and water flow flushing resistance are achieved, and construction quality and safety are ensured.
Patent Information
- Application Number
- CN202411259566.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
The existing concrete has a low strength when poured underwater and is prone to separating water, resulting in a reduced application quality of the specimens for underwater construction.
A formula for underwater premature filler, including silicate cement, composite fly ash, premature strength agent, sodium hydrogen phosphate, water reducer, hollow microbeads, carboxymethylcellulose, polyacrylamide and digestion Foaming agents are prepared by specific stirring and drying processes to form fillers with high early strength and resistance to water flow flux.
It achieves rapid strength formation underwater, ensures structural stability and safety, and improves permeability and compactness, significantly improving the early strength and durability of the filler.
Smart Images

Figure CN119118598A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of filling materials, in particular to an underwater early-strength filling material. Background Art
[0002] With the continuous development of society, more and more underwater construction projects are involved. Therefore, underwater early-strength filling materials have been promoted to a certain extent.
[0003] Underwater early strength filler is a special material specially used for underwater environment construction. It can maintain good stability and strength development characteristics underwater. The following is a detailed introduction to underwater early strength filler:
[0004] Underwater early strength filling materials are widely used in various engineering fields that require underwater pouring, including but not limited to: ① The construction of underwater structures such as caisson bottom sealing, cofferdams, and caissons;
[0005] ② Underwater continuous wall pouring, underwater foundation leveling and filling;
[0006] ③ Construction and maintenance of large-diameter cast-in-place piles, docks, dams and other water conservancy projects;
[0007] ④ Construction of complex underwater projects such as submarine tunnels and bridge foundations;
[0008] ⑤ Underwater repair projects such as reservoir repair, drainage outlet waterproofing and impact reinforcement of bottom plates, etc.
[0009] However, ordinary concrete has low strength and is prone to segregation and bleeding when poured underwater, which results in the strength not being guaranteed and reduces the application quality of the specimens made underwater.
[0010] Based on this, an underwater early strength filling material is provided to solve the existing technical problems. Summary of the invention
[0011] The purpose of the present invention is to provide an underwater early-strength filling material to solve the deficiencies in the prior art.
[0012] The technical solution adopted by the present invention is as follows:
[0013] An underwater early strength filler comprises the following components by weight: 500-550 parts of cement, 180-230 parts of composite fly ash, 2-4 parts of early strength agent, 1-3 parts of hydrogen phosphate, 1-3 parts of water reducer, 20-35 parts of hollow microspheres, 40-46 parts of carboxymethyl cellulose, 10-12 parts of polyacrylamide, 1-1.5 parts of defoamer, and 200-230 parts of water;
[0014] The cement is Portland cement;
[0015] Wherein, the hydrogen phosphate is sodium hydrogen phosphate;
[0016] The diameter of the hollow microspheres is 100 μm.
[0017] As a further technical solution: the preparation method of the composite fly ash is:
[0018] Modifier preparation:
[0019] Sodium polyacrylate and sodium alginate solid powders are sequentially added to water, and stirred and mixed to dissolve at room temperature to obtain a uniform mixed solution, which is the modifier;
[0020] Among them, the stirring speed is 100r / min;
[0021] First, the fly ash is added to the alkaline treatment liquid, the temperature is adjusted to 80°C, and the solution is stirred in a water bath for 40 minutes. Then, the solution is filtered, washed to neutrality, and dried to obtain the pretreated fly ash.
[0022] Among them, the speed of heat preservation and stirring is 500r / min;
[0023] The pretreated fly ash and the modifier are mixed, the temperature is adjusted to 68°C, and the mixture is stirred in a water bath for 4 hours to obtain a mixed slurry;
[0024] Among them, the speed of heat preservation and stirring is 200r / min;
[0025] Add calcium chloride solution dropwise to the mixed slurry, and continue stirring for 1 hour after the addition is completed to obtain a composite slurry;
[0026] The composite slurry is placed in a drying oven for 24 hours and then crushed to obtain composite fly ash.
[0027] Among them, the drying temperature in the drying oven is 100°C.
[0028] As a further technical solution: the mass fraction of sodium polyacrylate in the modifier is 8-10%;
[0029] The mass fraction of sodium alginate in the modifier is 1-2%.
[0030] As a further technical solution: the fly ash and alkaline treatment liquid are mixed in a ratio of 100 g: 200-250 mL;
[0031] The alkaline treatment solution preparation method is:
[0032] Sodium hydroxide, potassium hydroxide and sodium carbonate are added to water respectively, and stirred and mixed evenly to obtain an alkaline treatment solution;
[0033] Among them, the mixing mass ratio of sodium hydroxide, potassium hydroxide, sodium carbonate and water is 5:1:3:30.
[0034] As a further technical solution, the mixing ratio of the pretreated fly ash and the modifier is 30-40g:100mL.
[0035] As a further technical solution, the mixed slurry and calcium chloride solution are mixed in a volume ratio of 10:1;
[0036] Wherein, the mass fraction of calcium chloride solution is 5%.
[0037] As a further technical solution, the early strength agent is triethanolamine.
[0038] As a further technical solution, the water reducer is a polycarboxylic acid water reducer.
[0039] As a further technical solution, the defoaming agent is a silicone defoaming agent.
[0040] A method for preparing an underwater early-strength filling material comprises the following steps:
[0041] S1 weighs by weight: cement, composite fly ash, early strength agent, sodium hydrogen phosphate, water reducing agent, hollow microspheres, carboxymethyl cellulose, polyacrylamide, and water;
[0042] S2: cement, composite fly ash, early strength agent, sodium hydrogen phosphate, water reducing agent, hollow microspheres, carboxymethyl cellulose and polyacrylamide are added to a stirring mixer in sequence, and stirred and mixed for 1 hour to obtain a mixed material;
[0043] Among them, the stirring speed is 200r / min;
[0044] S3. Add water to the mixture and continue stirring for 4 hours to obtain an underwater early strength filling material;
[0045] Among them, the stirring speed is 60r / min.
[0046] Beneficial effects:
[0047] The underwater early-strength filler prepared by the present invention can quickly form strength to meet the needs of underwater construction. Through the coordination of various components, the filler can also achieve high early strength underwater to ensure the stability and safety of the structure. At the same time, the underwater early-strength filler prepared by the present invention usually has excellent resistance to water flow dispersion and can ensure the uniformity and stability of the filler components.
[0048] The invention uses silicate cement as the main cementitious material, so as to provide basic strength and bonding force, and the silicate cement has higher early strength and hydration heat.
[0049] The use of early strength agent can promote the early hydration reaction of cement, accelerate the formation of early strength of filler, and improve the quality of early strength filler.
[0050] The composite fly ash prepared by the present invention can effectively fill the pores and voids in the early strength filler structure. In the special environment of underwater early strength fillers, this filling effect is particularly important, which helps to reduce the erosion of water on the structure of the early strength filler and improve the compactness and impermeability of the early strength filler. The composite fly ash has volcanic ash properties, and its siliceous or silicoaluminous components can react with calcium hydroxide at room temperature to generate gelling hydration products. These hydration products can be interwoven with the hydration products of cement to form a denser network structure, thereby improving the strength and durability of concrete, especially in underwater environments. The continuous progress of this chemical reaction helps to enhance the impermeability and stability of the early strength filler, greatly improving its early strength, and as time goes by, the active ingredients in the composite fly ash continuously react with the calcium hydroxide generated by cement hydration to generate more hydration products, thereby further continuously improving the strength of the early strength filler.
[0051] The introduction of polycarboxylic acid water-reducing agent can achieve excellent water-reducing effect, which can significantly reduce water consumption while maintaining the working performance of the filler, thereby improving the strength and durability of the filler. In addition, the use of polycarboxylic acid water-reducing agent can also improve the workability of concrete, making the underwater construction of the filler smoother and ensuring the quality of the product after the filler is cured.
[0052] The introduction of hollow microspheres can improve the strength of the filler. At the same time, hollow microspheres can also improve the fluidity and pumping performance of the filler to a certain extent.
[0053] The introduction of defoaming agent is mainly to eliminate the bubbles generated during the stirring process of the filler, so as to improve the density and appearance quality of the filler. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 It is a bar chart of the 7d compressive strength of each test group. DETAILED DESCRIPTION
[0055] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] Example 1
[0057] A method for preparing an underwater early-strength filling material comprises the following steps:
[0058] S1 weighed by weight: 500 parts of Portland cement, 180 parts of composite fly ash, 2 parts of triethanolamine, 1 part of sodium hydrogen phosphate, 1 part of polycarboxylic acid water reducer, 20 parts of hollow microspheres, 40 parts of carboxymethyl cellulose, 10 parts of polyacrylamide, 1 part of organosilicon defoamer, and 200 parts of water;
[0059] The diameter of the hollow microspheres is 100 μm.
[0060] The preparation method of composite fly ash is as follows:
[0061] Modifier preparation:
[0062] Sodium polyacrylate and sodium alginate solid powders are sequentially added to water, and stirred and mixed to dissolve at room temperature to obtain a uniform mixed solution, which is the modifier;
[0063] Among them, the stirring speed is 100r / min;
[0064] First, the fly ash is added to the alkaline treatment liquid, the temperature is adjusted to 80°C, and the solution is stirred in a water bath for 40 minutes. Then, the solution is filtered, washed to neutrality, and dried to obtain the pretreated fly ash.
[0065] Among them, the speed of heat preservation and stirring is 500r / min;
[0066] The pretreated fly ash and the modifier are mixed, the temperature is adjusted to 68°C, and the mixture is stirred in a water bath for 4 hours to obtain a mixed slurry;
[0067] Among them, the speed of heat preservation and stirring is 200r / min;
[0068] Add calcium chloride solution dropwise to the mixed slurry, and continue stirring for 1 hour after the addition is completed to obtain a composite slurry;
[0069] The composite slurry is placed in a drying oven for 24 hours and then crushed to obtain composite fly ash.
[0070] Among them, the drying temperature in the drying oven is 100°C.
[0071] The mass fraction of sodium polyacrylate in the modifier is 8%;
[0072] The mass fraction of sodium alginate in the modifier is 1%.
[0073] The mixing ratio of fly ash and alkaline treatment liquid is: 100g:200mL;
[0074] The alkaline treatment solution preparation method is:
[0075] Sodium hydroxide, potassium hydroxide and sodium carbonate are added to water respectively, and stirred and mixed evenly to obtain an alkaline treatment solution;
[0076] Among them, the mixing mass ratio of sodium hydroxide, potassium hydroxide, sodium carbonate and water is 5:1:3:30.
[0077] The mixing ratio of pretreated fly ash and modifier is 30g:100mL.
[0078] The volume ratio of the mixed slurry and calcium chloride solution is 10:1;
[0079] Wherein, the mass fraction of calcium chloride solution is 5%.
[0080] S2: cement, composite fly ash, early strength agent, sodium hydrogen phosphate, water reducing agent, hollow microspheres, carboxymethyl cellulose and polyacrylamide are added to a stirring mixer in sequence, and stirred and mixed for 1 hour to obtain a mixed material;
[0081] Among them, the stirring speed is 200r / min;
[0082] S3. Add water to the mixture and continue stirring for 4 hours to obtain an underwater early strength filling material;
[0083] Among them, the stirring speed is 60r / min.
[0084] Example 2
[0085] A method for preparing an underwater early-strength filling material comprises the following steps:
[0086] S1 weighed by weight: 520 parts of Portland cement, 190 parts of composite fly ash, 2.5 parts of triethanolamine, 2 parts of sodium hydrogen phosphate, 2 parts of polycarboxylic acid water reducer, 25 parts of hollow microspheres, 42 parts of carboxymethyl cellulose, 11 parts of polyacrylamide, 1.2 parts of organosilicon defoamer, and 210 parts of water;
[0087] The diameter of the hollow microspheres is 100 μm.
[0088] The preparation method of composite fly ash is as follows:
[0089] Modifier preparation:
[0090] Sodium polyacrylate and sodium alginate solid powders are sequentially added to water, and stirred and mixed to dissolve at room temperature to obtain a uniform mixed solution, which is the modifier;
[0091] Among them, the stirring speed is 100r / min;
[0092] First, the fly ash is added to the alkaline treatment liquid, the temperature is adjusted to 80°C, and the solution is stirred in a water bath for 40 minutes. Then, the solution is filtered, washed to neutrality, and dried to obtain the pretreated fly ash.
[0093] Among them, the speed of heat preservation and stirring is 500r / min;
[0094] The pretreated fly ash and the modifier are mixed, the temperature is adjusted to 68°C, and the mixture is stirred in a water bath for 4 hours to obtain a mixed slurry;
[0095] Among them, the speed of heat preservation and stirring is 200r / min;
[0096] Add calcium chloride solution dropwise to the mixed slurry, and continue stirring for 1 hour after the addition is completed to obtain a composite slurry;
[0097] The composite slurry is placed in a drying oven for 24 hours and then crushed to obtain composite fly ash.
[0098] Among them, the drying temperature in the drying oven is 100°C.
[0099] The mass fraction of sodium polyacrylate in the modifier is 8.5%;
[0100] The mass fraction of sodium alginate in the modifier is 1.5%.
[0101] The mixing ratio of fly ash and alkaline treatment liquid is: 100g:220mL;
[0102] The alkaline treatment solution preparation method is:
[0103] Sodium hydroxide, potassium hydroxide and sodium carbonate are added to water respectively, and stirred and mixed evenly to obtain an alkaline treatment solution;
[0104] Among them, the mixing mass ratio of sodium hydroxide, potassium hydroxide, sodium carbonate and water is 5:1:3:30.
[0105] The mixing ratio of pretreated fly ash and modifier is 35g:100mL.
[0106] The volume ratio of the mixed slurry and calcium chloride solution is 10:1;
[0107] Wherein, the mass fraction of calcium chloride solution is 5%.
[0108] S2: cement, composite fly ash, early strength agent, sodium hydrogen phosphate, water reducing agent, hollow microspheres, carboxymethyl cellulose and polyacrylamide are added to a stirring mixer in sequence, and stirred and mixed for 1 hour to obtain a mixed material;
[0109] Among them, the stirring speed is 200r / min;
[0110] S3. Add water to the mixture and continue stirring for 4 hours to obtain an underwater early strength filling material;
[0111] Among them, the stirring speed is 60r / min.
[0112] Example 3
[0113] A method for preparing an underwater early-strength filling material comprises the following steps:
[0114] S1 weighed by weight: 530 parts of Portland cement, 200 parts of composite fly ash, 3 parts of triethanolamine, 2 parts of sodium hydrogen phosphate, 1.5 parts of polycarboxylic acid water reducer, 30 parts of hollow microspheres, 45 parts of carboxymethyl cellulose, 11 parts of polyacrylamide, 1.2 parts of organosilicon defoamer, and 220 parts of water;
[0115] The diameter of the hollow microspheres is 100 μm.
[0116] The preparation method of composite fly ash is as follows:
[0117] Modifier preparation:
[0118] Sodium polyacrylate and sodium alginate solid powders are sequentially added to water, and stirred and mixed to dissolve at room temperature to obtain a uniform mixed solution, which is the modifier;
[0119] Among them, the stirring speed is 100r / min;
[0120] First, the fly ash is added to the alkaline treatment liquid, the temperature is adjusted to 80°C, and the solution is stirred in a water bath for 40 minutes. Then, the solution is filtered, washed to neutrality, and dried to obtain the pretreated fly ash.
[0121] Among them, the speed of heat preservation and stirring is 500r / min;
[0122] The pretreated fly ash and the modifier are mixed, the temperature is adjusted to 68°C, and the mixture is stirred in a water bath for 4 hours to obtain a mixed slurry;
[0123] Among them, the speed of heat preservation and stirring is 200r / min;
[0124] Add calcium chloride solution dropwise to the mixed slurry, and continue stirring for 1 hour after the addition is completed to obtain a composite slurry;
[0125] The composite slurry is placed in a drying oven for 24 hours and then crushed to obtain composite fly ash.
[0126] Among them, the drying temperature in the drying oven is 100°C.
[0127] The mass fraction of sodium polyacrylate in the modifier is 8.5%;
[0128] The mass fraction of sodium alginate in the modifier is 1.8%.
[0129] The mixing ratio of fly ash and alkaline treatment liquid is: 100g:230mL;
[0130] The alkaline treatment solution preparation method is:
[0131] Sodium hydroxide, potassium hydroxide and sodium carbonate are added to water respectively, and stirred and mixed evenly to obtain an alkaline treatment solution;
[0132] Among them, the mixing mass ratio of sodium hydroxide, potassium hydroxide, sodium carbonate and water is 5:1:3:30.
[0133] The mixing ratio of pretreated fly ash and modifier is 38g:100mL.
[0134] The volume ratio of the mixed slurry and calcium chloride solution is 10:1;
[0135] Wherein, the mass fraction of calcium chloride solution is 5%.
[0136] S2: cement, composite fly ash, early strength agent, sodium hydrogen phosphate, water reducing agent, hollow microspheres, carboxymethyl cellulose and polyacrylamide are added to a stirring mixer in sequence, and stirred and mixed for 1 hour to obtain a mixed material;
[0137] Among them, the stirring speed is 200r / min;
[0138] S3. Add water to the mixture and continue stirring for 4 hours to obtain an underwater early strength filling material;
[0139] Among them, the stirring speed is 60r / min.
[0140] Example 4
[0141] A method for preparing an underwater early-strength filling material comprises the following steps:
[0142] S1 weighed by weight: 540 parts of Portland cement, 210 parts of composite fly ash, 3 parts of triethanolamine, 2.5 parts of sodium hydrogen phosphate, 2 parts of polycarboxylic acid water reducer, 32 parts of hollow microspheres, 45 parts of carboxymethyl cellulose, 10 parts of polyacrylamide, 1.2 parts of organosilicon defoamer, and 225 parts of water;
[0143] The diameter of the hollow microspheres is 100 μm.
[0144] The preparation method of composite fly ash is as follows:
[0145] Modifier preparation:
[0146] Sodium polyacrylate and sodium alginate solid powders are sequentially added to water, and stirred and mixed to dissolve at room temperature to obtain a uniform mixed solution, which is the modifier;
[0147] Among them, the stirring speed is 100r / min;
[0148] First, the fly ash is added to the alkaline treatment liquid, the temperature is adjusted to 80°C, and the solution is stirred in a water bath for 40 minutes. Then, the solution is filtered, washed to neutrality, and dried to obtain the pretreated fly ash.
[0149] Among them, the speed of heat preservation and stirring is 500r / min;
[0150] The pretreated fly ash and the modifier are mixed, the temperature is adjusted to 68°C, and the mixture is stirred in a water bath for 4 hours to obtain a mixed slurry;
[0151] Among them, the speed of heat preservation and stirring is 200r / min;
[0152] Add calcium chloride solution dropwise to the mixed slurry, and continue stirring for 1 hour after the addition is completed to obtain a composite slurry;
[0153] The composite slurry is placed in a drying oven for 24 hours and then crushed to obtain composite fly ash.
[0154] Among them, the drying temperature in the drying oven is 100°C.
[0155] The mass fraction of sodium polyacrylate in the modifier is 9.58%;
[0156] The mass fraction of sodium alginate in the modifier is 1.2%.
[0157] The mixing ratio of fly ash and alkaline treatment liquid is: 100g:230mL;
[0158] The alkaline treatment solution preparation method is:
[0159] Sodium hydroxide, potassium hydroxide and sodium carbonate are added to water respectively, and stirred and mixed evenly to obtain an alkaline treatment solution;
[0160] Among them, the mixing mass ratio of sodium hydroxide, potassium hydroxide, sodium carbonate and water is 5:1:3:30.
[0161] The mixing ratio of pretreated fly ash and modifier is 35g:100mL.
[0162] The volume ratio of the mixed slurry and calcium chloride solution is 10:1;
[0163] Wherein, the mass fraction of calcium chloride solution is 5%.
[0164] S2: cement, composite fly ash, early strength agent, sodium hydrogen phosphate, water reducing agent, hollow microspheres, carboxymethyl cellulose and polyacrylamide are added to a stirring mixer in sequence, and stirred and mixed for 1 hour to obtain a mixed material;
[0165] Among them, the stirring speed is 200r / min;
[0166] S3. Add water to the mixture and continue stirring for 4 hours to obtain an underwater early strength filling material;
[0167] Among them, the stirring speed is 60r / min.
[0168] Example 5
[0169] A method for preparing an underwater early-strength filling material comprises the following steps:
[0170] S1 weighed by weight: 550 parts of Portland cement, 230 parts of composite fly ash, 4 parts of triethanolamine, 3 parts of sodium hydrogen phosphate, 3 parts of polycarboxylic acid water reducer, 35 parts of hollow microspheres, 46 parts of carboxymethyl cellulose, 12 parts of polyacrylamide, 1.5 parts of organosilicon defoamer, and 230 parts of water;
[0171] The diameter of the hollow microspheres is 100 μm.
[0172] The preparation method of composite fly ash is as follows:
[0173] Modifier preparation:
[0174] Sodium polyacrylate and sodium alginate solid powders are sequentially added to water, and stirred and mixed to dissolve at room temperature to obtain a uniform mixed solution, which is the modifier;
[0175] Among them, the stirring speed is 100r / min;
[0176] First, the fly ash is added to the alkaline treatment liquid, the temperature is adjusted to 80°C, and the solution is stirred in a water bath for 40 minutes. Then, the solution is filtered, washed to neutrality, and dried to obtain the pretreated fly ash.
[0177] Among them, the speed of heat preservation and stirring is 500r / min;
[0178] The pretreated fly ash and the modifier are mixed, the temperature is adjusted to 68°C, and the mixture is stirred in a water bath for 4 hours to obtain a mixed slurry;
[0179] Among them, the speed of heat preservation and stirring is 200r / min;
[0180] Add calcium chloride solution dropwise to the mixed slurry, and continue stirring for 1 hour after the addition is completed to obtain a composite slurry;
[0181] The composite slurry is placed in a drying oven for 24 hours and then crushed to obtain composite fly ash.
[0182] Among them, the drying temperature in the drying oven is 100°C.
[0183] The mass fraction of sodium polyacrylate in the modifier is 10%;
[0184] The mass fraction of sodium alginate in the modifier is 2%.
[0185] The mixing ratio of fly ash and alkaline treatment liquid is: 100g:250mL;
[0186] The alkaline treatment solution preparation method is:
[0187] Sodium hydroxide, potassium hydroxide and sodium carbonate are added to water respectively, and stirred and mixed evenly to obtain an alkaline treatment solution;
[0188] Among them, the mixing mass ratio of sodium hydroxide, potassium hydroxide, sodium carbonate and water is 5:1:3:30.
[0189] The mixing ratio of pretreated fly ash and modifier is 40g:100mL.
[0190] The volume ratio of the mixed slurry and calcium chloride solution is 10:1;
[0191] Wherein, the mass fraction of calcium chloride solution is 5%.
[0192] S2: cement, composite fly ash, early strength agent, sodium hydrogen phosphate, water reducing agent, hollow microspheres, carboxymethyl cellulose and polyacrylamide are added to a stirring mixer in sequence, and stirred and mixed for 1 hour to obtain a mixed material;
[0193] Among them, the stirring speed is 200r / min;
[0194] S3. Add water to the mixture and continue stirring for 4 hours to obtain an underwater early strength filling material;
[0195] Among them, the stirring speed is 60r / min.
[0196] Comparative Example 1:
[0197] Based on Example 1, the fly ash is not processed and the rest of the technical solutions remain unchanged.
[0198] Comparative Example 2:
[0199] Based on Example 1, no modifier is added during the preparation of the composite fly ash, and the rest of the technical solutions remain unchanged.
[0200] test:
[0201] The main chemical composition of cement is shown in Table 1:
[0202] Table 1
[0203] Element% <![CDATA[SiO2]]> 22.04 <![CDATA[Al2O3]]> 4.36 CaO 66.02 MgO 2.18 <![CDATA[K2O]]> 0.59 <![CDATA[Na2O]]> 0.25
[0204] The main chemical components of fly ash are shown in Table 2:
[0205] Table 2
[0206]
[0207]
[0208] The slump test of the example samples was carried out according to DL / T 5117-2021;
[0209] Table 3
[0210] Slump mm Example 1 225 Example 2 228 Example 3 230 Example 4 222 Example 5 224
[0211] It can be seen from Table 3 that the underwater early strength filling material prepared by the present invention has a more suitable slump.
[0212] According to DL / T 5117-2021, the specimens with the size of 200mm×200mm×200mm were formed underwater, and the compressive strength test was carried out after standard curing for 7 days, as shown in Table 4:
[0213] Table 4
[0214]
[0215]
[0216] It can be seen from Table 4 that the early strength filler prepared by the present invention has higher strength performance.
[0217] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.
Claims
1. An underwater early strength filler, It is characterized in that The composition includes the following ingredients by weight: 500-550 parts of cement, 180-230 parts of composite fly ash, 2-4 parts of early strength agent, 1-3 parts of hydrogen phosphate, 1-3 parts of water reducing agent, 20-35 parts of hollow microspheres, 40-46 parts of carboxymethyl cellulose, 10-12 parts of polyacrylamide, 1-1.5 parts of defoaming agent, and 200-230 parts of water; The cement is Portland cement; Wherein, the hydrogen phosphate is sodium hydrogen phosphate; The diameter of the hollow microspheres is 100 μm.
2. An underwater early strength filler according to claim 1, Features: The composite fly ash preparation method is: Modifier preparation: Sodium polyacrylate and sodium alginate solid powders are sequentially added to water, and stirred and mixed to dissolve at room temperature to obtain a uniform mixed solution, which is the modifier; Among them, the stirring speed is 100r / min; First, the fly ash is added to the alkaline treatment liquid, the temperature is adjusted to 80°C, and the solution is stirred in a water bath for 40 minutes. Then, the solution is filtered, washed to neutrality, and dried to obtain the pretreated fly ash. Among them, the speed of heat preservation and stirring is 500r / min; The pretreated fly ash and the modifier are mixed, the temperature is adjusted to 68°C, and the mixture is stirred in a water bath for 4 hours to obtain a mixed slurry; Among them, the speed of heat preservation and stirring is 200r / min; Add calcium chloride solution dropwise to the mixed slurry, and continue stirring for 1 hour after the addition is completed to obtain a composite slurry; The composite slurry is placed in a drying oven for 24 hours and then crushed to obtain composite fly ash. Among them, the drying temperature in the drying oven is 100°C.
3. An underwater early strength filler according to claim 2, Features: The mass fraction of sodium polyacrylate in the modifier is 8-10%; The mass fraction of sodium alginate in the modifier is 1-2%.
4. An underwater early strength filler according to claim 2, Features: The mixing ratio of fly ash and alkaline treatment liquid is: 100g: 200-250mL; The alkaline treatment solution preparation method is: Sodium hydroxide, potassium hydroxide and sodium carbonate are added to water respectively, and stirred and mixed evenly to obtain an alkaline treatment solution; Among them, the mixing mass ratio of sodium hydroxide, potassium hydroxide, sodium carbonate and water is 5:1:3:
30.
5. An underwater early strength filling material according to claim 2, It is characterized in that The mixing ratio of the pretreated fly ash and the modifier is 30-40 g:100 mL.
6. An underwater early strength filling material according to claim 4, It is characterized in that The mixed slurry and calcium chloride solution have a mixing volume ratio of 10:1; Wherein, the mass fraction of calcium chloride solution is 5%.
7. An underwater early strength filling material according to claim 4, It is characterized in that The early strength agent is triethanolamine.
8. An underwater early strength filling material according to claim 4, It is characterized in that The water reducing agent is a polycarboxylic acid water reducing agent.
9. An underwater early strength filling material according to claim 4, It is characterized in that The defoamer is an organosilicon defoamer.
10. An underwater early strength filling material according to claim 4, It is characterized in that The preparation method of the underwater early strength filling material comprises the following steps: S1 weighs by weight: cement, composite fly ash, early strength agent, sodium hydrogen phosphate, water reducing agent, hollow microspheres, carboxymethyl cellulose, polyacrylamide, defoaming agent, and water; S2: cement, composite fly ash, early strength agent, sodium hydrogen phosphate, water reducing agent, hollow microspheres, carboxymethyl cellulose, polyacrylamide, and defoaming agent are added to a stirring mixer in sequence, and stirred and mixed for 1 hour to obtain a mixed material; Among them, the stirring speed is 200r / min; S3. Add water to the mixture and continue stirring for 4 hours to obtain an underwater early strength filling material; Among them, the stirring speed is 60r / min.
